Optimization of protein expression of alpha glucosidase from anoxybacillus - Tang, Jiaa Earn, 1990-, author; Goh, Kian Mau, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Project Paper (Sarjana Muda Sains (Biologi Industri)) - - Universiti Terknologi Malaysia, 2014